2019
DOI: 10.1097/ccm.0000000000003649
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Positive End-Expiratory Pressure and Spontaneous Breathing Activity on Regional Lung Inflammation in Experimental Acute Respiratory Distress Syndrome

Abstract: Objective: To determine the impact of positive end-expiratory pressure (PEEP) during mechanical ventilation with and without spontaneous breathing (SB) activity on regional lung inflammation in experimental non-severe ARDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 38 publications
4
27
0
1
Order By: Relevance
“…The present paper stresses the importance of the choice of PEEP during the modalities of ventilation that allows SB. As shown in a very recent PET study, SB per se does not increase lung inflammation when compared with controlled ventilation with an analogous ventilatory setup; it is the choice of PEEP that can deviate the clinical course toward an inflammatory status (Kiss et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…The present paper stresses the importance of the choice of PEEP during the modalities of ventilation that allows SB. As shown in a very recent PET study, SB per se does not increase lung inflammation when compared with controlled ventilation with an analogous ventilatory setup; it is the choice of PEEP that can deviate the clinical course toward an inflammatory status (Kiss et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…In order to measure regional transpulmonary pressures, three custom-made pressure sensors were attached to the parietal pleura in the following regions of the left hemithorax: (1) ventral (4-5th rib parasternal), (2) dorsal (4-5th rib paravertebral), and (3) caudal (8-9th rib paravertebral) as described in detail before (Kiss et al, 2019). Briefly, animals were positioned in the right lateral decubitus position.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Airway/tracheal pressure (P), airflow, and volume were recorded for 5 min at the end of each time point. Airway pressure and pleural pressure signals in ventral, dorsal, and caudal regions were obtained from pressure transducers [17] (163PC01D48-PCB, First-Sensors AG, Berlin, Germany). Respiratory system compliance and resistance were determined using multiple linear regression of the linear equation of motion composed of resistance R and compliance C two-compartmental model of the respiratory system.…”
Section: Respiratory Signals and Regional Pleural Pressurementioning
confidence: 99%
“…Global and regional lung metabolic activity were measured by 18 F-FDG uptake, a reliable biomarker of inflammation in the lung [ 32 ]. This marker is indicative of neutrophil activation in acute lung injury and ARDS [ 33 35 ]. Previous studies have shown that voxelwise ratio of lung parenchyma and air content influences 18 F-FDG uptake quantification, requiring normalization for the tissue fraction [ 26 , 36 ], which was performed in the current study.…”
Section: Discussionmentioning
confidence: 99%